ANALISIS IMPLEMENTASI METODE STORYTELLING TERHADAP KEMAMPUAN BERBICARA SISWA PADA PEMBELAJARAN BAHASA INDONESIA DI KELAS IV SDN I KAYANGAN KABUPATEN LOMBOK UTARA TAHUN AJARAN 2023/2024 - ILAWATI; Rahayu, Fitriani; Alawiyah, Tuti (Lembaga Bale Literasi, 2024)
Abstract Ilawati (2024). This research is a type of descriptive qualitative research entitled Analysis of the Implementation of the Storytelling Method on Students' Speaking Ability in Indonesian Language Learning in Class IV of Kayangan 1 State Elementary School for the 2023/2024 Academic Year. This research aims to analyze the implementation of storytelling methods which include; firstly, planning the application of the storytelling method to students' speaking skills, secondly, implementation of the application of the storytelling method to students' speaking abilities in Indonesian language learning and also to analyze the impact or implications of the storytelling method on students' speaking abilities. The results of this research show that: first, planning the application of the storytelling method to speaking skills includes: materials, media, strategies and techniques. Second, the implementation of the application of the storytelling method on speaking skills through several stages, namely the opening stage, the story telling stage, and the closing stage and the impact of the application of the storytelling method on speaking skills, namely the students' courageous attitude and appearing confident when speaking in front, mastery of vocabulary , enthusiasm and students' moral attitudes. Meanwhile, teachers can really help and make teaching and learning activities easier. Keywords: Storytelling Method, Speaking Ability, Indonesian language